ASSESSMENT TECHNIQUES ADMINISTERED IN ENGLISHLANGUAGE CLASSROOM FOR YOUNG LEARNERS : A Descriptive Research Conducted in Primary Schools in Bandung Kulon - Siti Masitoh, - (2008)
Some conclusions are drawn from the research related to aspects assessed, assessment techniques used, and reasons for choosing assessment techniques. They are as follows. In terms of aspects assessed, linguistics aspects mostly assessed in traditional tests, oral test, take-home tasks, and portfolio. Compared to linguistics aspects, non-linguistics aspects were assessed through observation. The traditional tests were mainly used as assessment technique because of their practicality. In order to get a reliable picture of learners' ability, oral tests, take home tasks, observation and portfolio have been considered together with traditional tests. Assessment techniques used and aspects assessed conducted by the teachers in their classes seemed varied from another. CHAPTERV CONCLUSIONS AND SUGGESTIONS Aspects assessed and assessment techniques used, however, were not ample in gaining information about students' progress and achievement. It seemed that the teachers have inadequate knowledge and ability to implement assessment techniques in their classroom. Prevailed by a mismatch was found. The teachers' beliefs about assessment techniques but their beliefs are not same as what assessment techniques in practices are. Hence, the teacher's beliefs and 52 knowledge impact on the assessment techniques used in practice. The teachers can optimize the assessment through attending seminar or training. However, it seemed the teachers do not have access to achieve information dealing with any assessment they are expected to implement. As evidenced by training or seminar related to assessment is rarely conducted. Hence, training or seminar about assessing young learners is required to be held.